Kolonialisme Vis a Vis Nasionalisme Perspektif Hadis - M. Kharis Majid; Salamah Noorhidayati (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2023)
The words colonialism, imperialism and feudalism are conditioned by nature and attitude rather than tyranny. This is in stark contrast to Islam as a religion that strongly rejects actions that afflict others. This paper aims to find out, how the anticolonialism movement in Islam through nationalism is instilled with a ḥadīts perspective. In this article, the author uses an analytical descriptive method, namely by exposing ḥadīts related to colonialism and nationalism as a counterpoint, then explaining them by analyzing existing ḥadīts. So it can find nationalism in Islam as an anti-colonialism movement. The result of this paper is that in Islam there are two interesting concepts in the rejection of this movement, namely the concept of nationalism and the concept of jihad. Nationalism as a reinforcement of the nation's self-identity will give rise to a fanatical attitude towards the country which will certainly reject colonialism. Meanwhile, jihad in Islam is related to Muslim attitudes towards tyranny carried out by the colonials.